West African Economic and Monetary Union : Financial Sector Assessment Program-Technical Note on Analysis of Systemic Liquidity. (IMF Staff Country Reports; Country Report, 2022)
The limited development of markets in the region represents a key risk factor for financial stability. 1 Since the previous Financial Sector Assessment Program (FSAP) in 2008, the bank deposit base has increased from 18 percent to 30 percent of gross domestic product (GDP) and the buoyancy of the government securities market has benefited from the interruption of public deficit financing by the Central Bank of West African States (BCEAO). Nevertheless, a significant portion of bank funding cannot be considered stable, due to the concentration of deposits held by large corporations. Apart from reserves held with the BCEAO, banks have little in the way of liquid assets, although the secondary market for government securities is beginning to grow for some issuers. Insufficient secondary market liquidity and the prevalence of unsecured intragroup transactions (60 percent of the total) in the interbank market exacerbate the risk and extent of potential losses for banks in the event of liquidity distress.